2021
DOI: 10.1080/00140139.2020.1870162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of industrial back-support exoskeletons on body loading and user experience: an updated systematic review

Abstract: This study is an updated systematic review of papers published in the last five years on industrial back-support exoskeletons. The research questions were aimed at addressing the recent findings regarding objective (e.g. body loading, user performance) and subjective evaluations (e.g. user satisfaction), potential side effects, and methodological aspects of usability testing. Thirteen studies of active and twenty of passive exoskeletons were identified. The exoskeletons were tested during lifting and bending t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 53 publications
7
132
1
Order By: Relevance
“…This modification of LiFFT is logical because the back moment provided by the exo reduces that moment borne by the biological back extensors (e.g., muscles, ligaments). This biological offloading is well supported by prior literature using electromyography (EMG), force-instrumentation, and musculoskeletal modeling (Bär et al, 2021;Howard et al, 2020;Kermavnar et al, 2020;Lamers and Zelik, 2021). For instance, Lamers et al (2020) evaluated assistance benefits of a soft, passive-elastic back exo using two separate analyses -EMG, and a physics-based moment balance -and found the magnitude of back offloading estimated by each analysis to be similar.…”
Section: Exo-lifft For Ergonomic Assessment Of Back Injury Risk and Damage While Wearing Exosmentioning
confidence: 54%
See 3 more Smart Citations
“…This modification of LiFFT is logical because the back moment provided by the exo reduces that moment borne by the biological back extensors (e.g., muscles, ligaments). This biological offloading is well supported by prior literature using electromyography (EMG), force-instrumentation, and musculoskeletal modeling (Bär et al, 2021;Howard et al, 2020;Kermavnar et al, 2020;Lamers and Zelik, 2021). For instance, Lamers et al (2020) evaluated assistance benefits of a soft, passive-elastic back exo using two separate analyses -EMG, and a physics-based moment balance -and found the magnitude of back offloading estimated by each analysis to be similar.…”
Section: Exo-lifft For Ergonomic Assessment Of Back Injury Risk and Damage While Wearing Exosmentioning
confidence: 54%
“…We recommend the use of physics-based (lumbar moment) analysis for assessing back exos, particularly for devices or assistance levels where EMG studies have already been conducted that confirm consistency with moment-based estimates, and where evidence exists indicating there is not substantial co-contraction of the abdominal muscles or major changes to lifting kinematics. Of note, most studies on back exos have not observed abdominal muscle activity to increase during lifting or bending (Kermavnar et al, 2020). For instance, Lamers et al (2020) found no substantial changes to abdominal muscle activity with vs. without a soft, passive-elastic back exo, and that abdominal EMG did not exceed 5% maximum voluntary contraction with or without the exo.…”
Section: The Need and Benefit Of Keeping Ergonomic Assessment Tools As Simple As Practicalmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Tsuzura et al (2013) proposed a motordriven power suit to help caregivers lift and move heavy objects. A more recent review of the scientific evidence on back support exoskeletons found 13 additional studies and reported decreases in back muscle activity and spinal compression forces but performance tended to decline where tasks required more agile movements (Kermavnar et al, 2021). However, the majority of these studies were tested in a laboratory with healthy subjects and none were demonstrated in healthcare.…”
mentioning
confidence: 99%